A Philosophical Cum Religious Conversation on the Impact of Artificial Intelligence on Digital Humanities - Uzoigwe, Elias Ifeanyi; Chukwuma-Offor, Amara Mary (dialektika kontemporer, 2025)
This conversation explores the impact of Artificial Intelligence (AI) on the field of Digital Humanities, particularly through the lenses of philosophy and religion. The 21st century has witnessed AI technologies revolutionize the way humans engage with knowledge, ethical issues, and cultural concerns. The study examines how AI facilitates new avenues for interpreting religious texts, preserving sacred traditions, and reflecting on existential issues. The integration of AI and digital humanities offers significant opportunities for enhancing human understanding of religious doctrines, historical narratives, and moral issues. However, this advancement also raises critical questions regarding the ethical implications of machine-driven interpretations and the potential challenges posed to spiritual beliefs and human agency. This reflection, which employs the method of critical analysis navigates the interconnectedness of the sacred and the artificial, addressing the prospects, challenges, and ethical quandaries inherent in the convergence of AI with philosophy and religion in the competitive and digital world.